2011
DOI: 10.1007/s10557-011-6354-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrates and Other Nitric Oxide Donors in Cardiology - Current Positioning and Perspectives

Abstract: Nitric oxide donors have been commonly used in the therapy of cardiovascular disease for more than 150 years. In spite of this longevity and the popularity of their use, it appears somewhat paradoxical that there is no current consistent use among cardiologists, as to both their indications and their optimal mode of administration. In part this results from their contradictory pharmacodynamics: when given acutely, their effectiveness is undisputable; however, their long-term efficacy is potentially limited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Organic nitrates, generally referred to as nitrovasodilatators, have been used for over a century in cardiovascular therapy and to date are still largely used in the treatment of several cardiovascular diseases . These drugs are known as nitric oxide (NO) donors and have mainly an arterial and venous dilatation effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic nitrates, generally referred to as nitrovasodilatators, have been used for over a century in cardiovascular therapy and to date are still largely used in the treatment of several cardiovascular diseases . These drugs are known as nitric oxide (NO) donors and have mainly an arterial and venous dilatation effect.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and ex vivo studies have also demonstrated an effect on hemostatic system of NO donors mediated by different mechanisms that include the inhibition of platelet and leukocyte activation . Nitric oxide donors may reduce neutrophil adhesion to the endothelium and inhibit the expression of platelet adhesion molecules and thus influence atherosclerotic plaque complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, from a therapeutic point of view, the restoration of adequate NO levels has been shown to revert endothelial dysfunction, improving cardiovascular wellness. However, the advances in NO donor drug development have been limited due to tolerance, appearance of side effects, and limited therapeutic improvements with respect to other classes of cardiovascular protective agents (Daiber et al, 2008;Iachini Bellisarii et al, 2012). Thus, there is a need for new generation of NO donor drugs to be used in an extended range of pathologies related to the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Current ESC HF guidelines accord a class IIa indication for administration of NO donors in patients admitted for acute HF with pulmonary edema without concomitant cardiogenic shock [201]. Unfortunately, long-term use of NO donors is frequently hampered by development of NO resistance [202]. NO resistance largely results from a combination of scavenging of NO by superoxide and of inactivation of sGC [203].…”
Section: No-donorsmentioning
confidence: 99%